2018
DOI: 10.4103/ijem.ijem_117_18
|View full text |Cite
|
Sign up to set email alerts
|

The twin white herrings: Salt and sugar

Abstract: India has the dubious distinction of being a hotspot for both diabetes and hypertension. Increased salt and sugar consumption is believed to fuel these two epidemics. This review is an in-depth analysis of current medical literature on salt and sugar being the two white troublemakers of modern society. The PubMed, Medline, and Embase search for articles published in January 2018, using the terms “salt” [MeSH Terms] OR “sodium chloride” [All Fields] OR “sugar” [All Fields]. India is world's highest consumer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 101 publications
2
1
1
Order By: Relevance
“…As expected, increased rates of suboptimal diet behaviours were all found to have significant associations with increased BMI and waist circumference, consistent with findings in the general population that foods high in salt and sugar are associated with raised BMI, hypertension, and overall worsened cardiometabolic outcomes [53][54][55]. The correlation between increased salty snack serves and raised systolic and diastolic BP was also expected, as sodium intake has been shown to have a significant association with increased BP [4,53,55]. In women following a pregnancy affected by HDP, who are already at an increased risk of worsened cardiometabolic risk profiles, controlling dietary sodium and processed sugar intake via education or intervention could significantly improve their cardiometabolic health, and potentially reduce long-term CVD risk [53][54][55].…”
Section: Weight Outcomessupporting
confidence: 86%
See 2 more Smart Citations
“…As expected, increased rates of suboptimal diet behaviours were all found to have significant associations with increased BMI and waist circumference, consistent with findings in the general population that foods high in salt and sugar are associated with raised BMI, hypertension, and overall worsened cardiometabolic outcomes [53][54][55]. The correlation between increased salty snack serves and raised systolic and diastolic BP was also expected, as sodium intake has been shown to have a significant association with increased BP [4,53,55]. In women following a pregnancy affected by HDP, who are already at an increased risk of worsened cardiometabolic risk profiles, controlling dietary sodium and processed sugar intake via education or intervention could significantly improve their cardiometabolic health, and potentially reduce long-term CVD risk [53][54][55].…”
Section: Weight Outcomessupporting
confidence: 86%
“…Future interventions which target fruit and vegetable intake post-HDP have the potential to optimise cardiometabolic health and mitigate increased CVD risk in this population [16,33]. As expected, increased rates of suboptimal diet behaviours were all found to have significant associations with increased BMI and waist circumference, consistent with findings in the general population that foods high in salt and sugar are associated with raised BMI, hypertension, and overall worsened cardiometabolic outcomes [53][54][55]. The correlation between increased salty snack serves and raised systolic and diastolic BP was also expected, as sodium intake has been shown to have a significant association with increased BP [4,53,55].…”
Section: Weight Outcomessupporting
confidence: 77%
See 1 more Smart Citation
“…A past study by Mullie et al ( 45 ) concluded that functional food consumption was associated with healthy dietary pattern, which is characterised as high consumption of tomatoes, fruits, low-fat dairy products, whole grains, vegetables, cold breakfast cereals, fruit juice, fish, tea and nuts. However, this relation could not be confirmed in the present study as both salty snacks and soft drinks/SSB consumption were also found to be associated with the use of functional foods; and these foods are high in sugar and sodium, which are widely proven for their negative effects on human health, particularly increased risk of non-communicable diseases ( 46 ).…”
Section: Discussioncontrasting
confidence: 69%